THE INFLUENCE OF MEDITERRANEAN CYCLONES ON THE WEATHER IN OLTENIA DURING THE FIRST MONTH OF SUMMER - SFÎRLEAZĂ FANIA; BĂCESCU M.; BURADA CRISTINA; BRÂNCUȘ MIHAELA; IORDĂCHESCU Ş. (Aerul şi Apa: Componente ale Mediului, 2015)
Defining the Mediterranean cyclones as “semi-permanent centers” active only in the cold half of the year would suggest that they are not active in summer, and their influence on the weather of southern Europe and Romania is insignificant during this season. The statistical-climatological study presented in this paper shows that the daily frequency of occurrence of the Mediterranean cyclones during the month of June in the period 1981-2010, which influenced the weather in Oltenia, is 8%. Thus, they can be active all year round and can cause episodes of severe weather, depending on the position of other baric centers (the Azores High, The Icelandic Depression). Climatological aspects were investigated using meteorological data for June in the period 1981-2010, available from the quality check database of National Meteorological Administration, Bucharest. For describing the general context, climatological data was used to provide a global overview. Reanalysis data of sea-level pressure and geopotential height at 500 hPa, available from NOOA-NCEP/NCAR, were also used.